Total Quality Management Dan Pengaruhnya Terhadap Produktivitas Guru Di Ponpes Albarkah Sumenep - Wanda, Amelia Ayu (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2024)
This study aims to examine the implementation of Total Quality Management (TQM) and its impact on teacher productivity at Pondok Pesantren (Ponpes) Albarkah. Using a quantitative approach and descriptive-correlational design, the study involved 25 purposively selected teachers as the sample. Data were collected through questionnaires, interviews, and documentation. The results indicate a high level of TQM implementation at Ponpes Albarkah, particularly in continuous improvement and full involvement aspects. Supporting factors, such as organizational culture and management commitment, as well as barriers like limited facilities and administrative workload, influenced the success of TQM implementation. Correlation analysis shows a positive and significant relationship between TQM implementation and teacher productivity, with a contribution of 52% to productivity variability. Teachers at Ponpes Albarkah showed a positive perception of TQM, although some expressed concerns about additional administrative tasks. The positive impact of TQM on student learning outcomes is also reflected in the increased productivity of teachers, enabling them to adapt teaching methods to students' needs. Several strategies are suggested to optimize TQM implementation, including enhanced training, simplification of administrative workloads, and improved educational facilities. With optimal TQM implementation, the quality of education at Ponpes Albarkah is expected to improve continuously, supporting teacher productivity and meeting students' learning needs more effectively.